Risk Overhang and Loan Portfolio Decisions: Small Business Loan Supply before and during the Financial Crisis - DEYOUNG, ROBERT; GRON, ANNE; TORNA, GӦKHAN; WINTON, ANDREW (Journal of Finance, 2015)
ABSTRACT We estimate a structural model of bank portfolio lending and find that the typical U.S. community bank reduced its business lending during the global financial crisis. The decline in business credit was driven by increased risk overhang effects (consistent with a reduction in the liquidity of assets held on bank balance sheets) and by reduced loan supply elasticities suggestive of credit rationing (consistent with an increase in lender risk aversion). Nevertheless, we identify a group of strategically focused relationship banks that made and maintained higher levels of business loans during the crisis.